Tumor-promoting phorbol diesters cause the phosphorylation of epidermal growth factor receptors in normal human fibroblasts at threonine-654. - Davis, R J (1985)
The effect of tumor-promoting phorbol diesters to potentiate the action of epidermal growth factor (EGF) on cell proliferation is associated with phosphorylation of EGF receptors, acute depression of EGF binding, and inhibition of EGF receptor tyrosine kinase activity. In the present studies, normal human fibroblasts and A431 carcinoma cells were labeled with [32P]phosphate and treated with and without 10 nM 4 beta-phorbol 12 beta-myristate 13 alpha-acetate (PMA). The EGF receptors then were isolated by immunoprecipitation and digested with trypsin. Analysis of the labeled receptor phosphopeptides by reversed-phase HPLC revealed that PMA induces the phosphorylation of a unique phosphopeptide containing [32P]phosphothreonine. Comparison of several chemical and physical properties of the 32P-labeled phosphopeptide with the primary structure of the EGF receptor suggested the identify Lys-Arg-Thr(P)-Leu-Arg. This was confirmed by direct demonstration that a synthetic peptide of this structure comigrates during HPLC and electrophoresis with the 32P-labeled phosphopeptide isolated from the EGF receptors of normal human fibroblasts. The phosphorylated site on the peptide corresponds to threonine-654 of the EGF receptor, which is located on the cytoplasmic side of the plasma membrane nine residues distant from the transmembrane domain. These data indicate that phosphorylation of the EGF receptor in human fibroblasts and A431 cells at threonine-654 may regulate the EGF receptor tyrosine kinase activity and the binding of EGF.